ANALISIS PERBEDAAN FAKTOR YANG BERPENGARUH PADA KEPUASAN KERJA PERAWAT PNS DAN NON PNS DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO (Studi di RSUD Prof. Dr. Margono Soekarjo Purwokerto) - Vienda Wirani; Septo Pawelas Arso; Chriswardani Suryawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Job Satisfaction is an individual thing because each individual will have different level of satisfaction in accordance with the values preavailing in each individual. The nurse is one of the professions in the hospital, and a nurse will work productively depending on job satisfaction. The hospital with the blinds of BLUD divides the employees into two, namely civil servants and non civil servants. The purpose of this study is to analyze the differences of factors that affect the job satisfaction of civil servants and non civil servants in RSUD Prof. Dr. Margono Soekarjo Purwokerto. This research is a comparative descriptive research, with cross sectional study design. The population in this study were all nurses of civil servants and non civil servants. Research subjects selected using the slovin formula of 80 nurses civil servants and 80 nurses non civil servants. The result of this research shows that there are differences of job satisfactions factor of civil servants and non civil servants nurses on the forward opportunity variabels, recognition, salary and there not have differences is the work it self, achievment, responsibility, relationship between employess anda working conditions. Therefore, the hospital is expeted to pay more attention to the nurses of civil servants and non civil servants, especially on the forward opportunity, recognition, and salary, so that difference of job satisfaction can be handled so that nurses will work more productively and the performance will increase.